Alternative approaches for energy conservation in a sanitary-ware plant - Virush Teeraseranee; Pakorn Adulbhan; Tang, John C.S.; Tabucanon, Mario T.; Government of the Republic of Germany (Bangkok : Asian Institute of Technology, 1981)
The study reported herein is concerned with the energy conservation problem and the peak demand reduction of electricity in a sanitary-ware factory. It deals with the problem of determining what conservation measures are applicable to this factory, what the possible saving could be and how to reduce peak demand of electricity. Data and information related to the energy consumption of the factory were first collected and analyzed to arrive at estimates for the energy used per unit production and also to assist in the energy analysis of the factory. The areas where energy conservation measures could be taken have been identified. Economic evaluations have been performed and the potential saving estimated. Two models have been developed to plan the reduction of the peak demand. The first is a mathematical model which can be used to determine how to reschedule the deferable loads. The solution procedure of this model uses linear programing techniques. The second model determines the optimal time delays needed between the successive starting of each piece of equipment when work resumes after a power failure, if the maximum allowable peak demand is to be kept within an upper limit prescribed by the management.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Sanitary supply industry -- Thailand -- Energy conservation